Multiomics on mental stress-induced myocardial ischemia: A narrative review - Nana Jin; Lixin Cheng; Qingshan Geng (Heart and Mind, 2024)
Accumulating multiomics studies have been developed to gain new insights into complex diseases, including mental stress-induced diseases and myocardial ischemia. Multiomics techniques integrate multiple layers of biological data, such as genomics, transcriptomics, proteomics, and metabolomics, to obtain a more comprehensive understanding of the molecular mechanisms underlying these diseases. Despite the potential benefits of applying multiomics approaches to the study of mental stress-induced myocardial ischemia (MSIMI), such studies are relatively limited. The etiology of MSIMI remains poorly understood, highlighting the need for further research in this field. This review first discusses the current state of knowledge on MSIMI and highlights the research gaps in this field. Then, we provide an overview of recent studies that have used multiomics approaches to expand insights into mental stress-induced diseases and myocardial ischemia, respectively. Finally, we propose possible research directions that can be pursued to improve our knowledge of MSIMI and the potential benefits of applying multiomics approaches to this domain. While still in its early stages, multiomics research holds great promise for improving the recognition of MSIMI and developing more effective clinical interventions.